You're making me hate you : a cantankerous look at the common misconception that humans have any common sense left - Taylor, Corey, 1973- (Da Capo Press, 2015)
The lead singer of the bands Slipknot and Stone Sour humorously pokes fun at all of life's annoyances including the rude behavior of people in malls and restaurants, poor fashion decisions, air travel and the sad state of modern music.